PLAP-1/Asporin Positively Regulates FGF-2 Activity. (October 2015) - Awata, T.; Yamada, S.; Tsushima, K.; Sakashita, H.; Yamaba, S.; Kajikawa, T.; Yamashita, M.; Takedachi, M.; Yanagita, M.; Kitamura, M.; Murakami, S.
PLAP-1 is an extracellular matrix protein that is predominantly expressed in the periodontal ligament within periodontal tissue. It was previously revealed that PLAP-1 negatively regulates bone morphogenetic protein 2 and transforming growth factor β activity through direct interactions. However, the interaction between PLAP-1 and other growth factors has not been defined. Here, we revealed that PLAP-1 positively regulates the activity of fibroblast growth factor 2 (FGF-2), a critical growth factor in tissue homeostasis and repair. In this study, we isolated mouse embryonic fibroblasts (MEFs) from Plap-1 -/- mice generated in our laboratory. Interestingly, Plap-1 -/- MEFs exhibited enhanced responses to bone morphogenetic protein 2 but defective responses to FGF-2, and Plap-1 transfection into Plap-1 -/- MEFs rescued these defective responses. In addition, binding assays revealed that PLAP-1 promotes FGF-2–FGF receptor 1 (FGFR1) complex formation by direct binding to FGF-2. Immunocytochemistry analyses revealed colocalization of PLAP-1 and FGF-2 in wild-type MEFs and reduced colocalization of FGF-2 and FGFR1 in Plap-1 -/- MEFs compared with wild-type MEFs. Taken together, PLAP-1 positively regulates FGF-2 activity through a direct interaction. Extracellular matrix–growth factor interactions have considerable effects; thus, this approach may be useful in several regenerative medicine applications.